2023
DOI: 10.1038/s41536-023-00282-7
|View full text |Cite
|
Sign up to set email alerts
|

Murine neonatal cardiac B cells promote cardiomyocyte proliferation and heart regeneration

Abstract: The irreversible loss of cardiomyocytes in the adult heart following cardiac injury leads to adverse cardiac remodeling and ventricular dysfunction. However, the role of B cells in cardiomyocyte proliferation and heart regeneration has not been clarified. Here, we found that the neonatal mice with B cell depletion showed markedly reduced cardiomyocyte proliferation, leading to cardiac dysfunction, fibrosis scar formation, and the complete failure of heart regeneration after apical resection. B cell depletion a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Among these genes, some are characterized as pivotal heart regeneration regulators, such as the Notch signaling modulator lfng (P1: 2.5 fold, P8: 1.33 fold) [ 20 ], the immune cell infiltration regulator Cxcl1 (P1: 9.05 fold, P8: 3.17 fold) (Fig. S 1 H) [ 19 , 21 ], as well as secretory leukocyte peptidase inhibitor Slpi (P1: 7.80 fold, P8: 3.46 fold) [ 22 ], that function to promote cardiac remodeling or cardiomyocyte proliferation. Thus, the correlation between the attenuation of IRE activation and the decline in regenerative capacity implies that IREs might partly contribute to heart regeneration in mice, although this needs further experimental confirmation.…”
Section: Resultsmentioning
confidence: 99%
“…Among these genes, some are characterized as pivotal heart regeneration regulators, such as the Notch signaling modulator lfng (P1: 2.5 fold, P8: 1.33 fold) [ 20 ], the immune cell infiltration regulator Cxcl1 (P1: 9.05 fold, P8: 3.17 fold) (Fig. S 1 H) [ 19 , 21 ], as well as secretory leukocyte peptidase inhibitor Slpi (P1: 7.80 fold, P8: 3.46 fold) [ 22 ], that function to promote cardiac remodeling or cardiomyocyte proliferation. Thus, the correlation between the attenuation of IRE activation and the decline in regenerative capacity implies that IREs might partly contribute to heart regeneration in mice, although this needs further experimental confirmation.…”
Section: Resultsmentioning
confidence: 99%
“…Cardiac B cells in neonatal mice promote cardiomyocyte proliferation, angiogenesis, and regeneration of the heart and inhibit inflammatory responses, while adult B cells promote inflammation and impair cardiac function following myocardial injury ( Zouggari et al, 2013 ; Tan et al, 2023 ). Depletion of neonatal B cells reduces cardiac regeneration and promotes fibrotic scarring in the post-MI heart, whereas B-cell depletion in adult mice inhibits myocardial fibrosis and improves cardiac function ( Tan et al, 2023 ) . Moreover, activated B cells contribute to sustained immune system activation and myocardial inflammation, promote the synthesis of myocardial collagen types I and III, and damage the left ventricular ejection fraction ( Mo et al, 2021 ) .…”
Section: Contribution Of the Immune System To Cardiac Homeostasismentioning
confidence: 99%
“…(2) Bone marrow-derived naive B lymphocytes were found to improve cardiac function after MI in adult mice ( Xu et al, 2022 ). Certain distinct subsets of B cells can also play a beneficial role in the repair of cardiac injury, promoting cardiomyocyte regeneration via paracrine proteins, although this effect is insufficient to offset proinflammatory and profibrotic effects ( Tan et al, 2023 ). Single-cell RNA sequencing showed that cardiac B cells in postnatal day 1 mice exhibit increased abilities to inhibit inflammatory responses and promote angiogenesis and the clearance of cellular debris after myocardial injury( Figure 3B ) ( Tan et al, 2023 ).…”
Section: The Extracellular Microenvironment Of Cardiomyocytes Favors ...mentioning
confidence: 99%
“…Certain distinct subsets of B cells can also play a beneficial role in the repair of cardiac injury, promoting cardiomyocyte regeneration via paracrine proteins, although this effect is insufficient to offset proinflammatory and profibrotic effects ( Tan et al, 2023 ). Single-cell RNA sequencing showed that cardiac B cells in postnatal day 1 mice exhibit increased abilities to inhibit inflammatory responses and promote angiogenesis and the clearance of cellular debris after myocardial injury( Figure 3B ) ( Tan et al, 2023 ). Neonatal mice with B-cell depletion did not exhibit any signs of regeneration after apical resection; this sheds new light on the indispensable roles of neonatal B-cell subsets in heart regeneration( Figure 3B ) ( Tan et al, 2023 ).…”
Section: The Extracellular Microenvironment Of Cardiomyocytes Favors ...mentioning
confidence: 99%
See 1 more Smart Citation